Aportaciones en el estudio de la asimetría funcional - Bausela Herreras, Esperanza (Revista Complutense de Educación, 2006)
Several theoretical have analysed and studied the dichotomy cerebral. Benedet (1986) considers that the functional asymmetry is not conceptualized in terms dichotomy but if in terms of degrees. There isn’t a dominant hemisphere in front of a silent hemisphere. Today, it is known that each hemisphere has multiple possibilities and the question is if there are aptitudes to take to processing information differences for every hemisphere. It is this aspect in which we tare going to study in depth.